Biochemical and Physical Properties of the Methanococcus jannaschii 20S Proteasome and PAN, a Homolog of the ATPase (Rpt) Subunits of the Eucaryal 26S Proteasome - Wilson, Heather L. (American Society for Microbiology, 2000)
The 20S proteasome is a self-compartmentalized protease which degrades unfolded polypeptides and has been purified from eucaryotes, gram-positive actinomycetes, and archaea. Energy-dependent complexes, such as the 19S cap of the eucaryal 26S proteasome, are assumed to be responsible for the recognition and/or unfolding of substrate proteins which are then translocated into the central chamber of the 20S proteasome and hydrolyzed to polypeptide products of 3 to 30 residues. All archaeal genomes which have been sequenced are predicted to encode proteins with up to ∼50% identity to the six ATPase subunits of the 19S cap. In this study, one of these archaeal homologs which has been named PAN for proteasome-activating nucleotidase was characterized from the hyperthermophile Methanococcus jannaschii. In addition, the M. jannaschii 20S proteasome was purified as a 700-kDa complex by in vitro assembly of the α and β subunits and has an unusually high rate of peptide and unfolded-polypeptide hydrolysis at 100°C. The 550-kDa PAN complex was required for CTP- or ATP-dependent degradation of β-casein by archaeal 20S proteasomes. A 500-kDa complex of PAN(Δ1–73), which has a deletion of residues 1 to 73 of the deduced protein and disrupts the predicted N-terminal coiled-coil, also facilitated this energy-dependent proteolysis. However, this deletion increased the types of nucleotides hydrolyzed to include not only ATP and CTP but also ITP, GTP, TTP, and UTP. The temperature optimum for nucleotide (ATP) hydrolysis was reduced from 80°C for the full-length protein to 65°C for PAN(Δ1–73). Both PAN protein complexes were stable in the absence of ATP and were inhibited by N-ethylmaleimide and p-chloromercuriphenyl-sulfonic acid. Kinetic analysis reveals that the PAN protein has a relatively high V(max) for ATP and CTP hydrolysis of 3.5 and 5.8 μmol of P(i) per min per mg of protein as well as a relatively low affinity for CTP and ATP with K(m) values of 307 and 497 μM compared to other proteins of the AAA family. Based on electron micrographs, PAN and PAN(Δ1–73) apparently associate with the ends of the 20S proteasome cylinder. These results suggest that the M. jannaschii as well as related archaeal 20S proteasomes require a nucleotidase complex such as PAN to mediate the energy-dependent hydrolysis of folded-substrate proteins and that the N-terminal 73 amino acid residues of PAN are not absolutely required for this reaction.